The successful use of therapeutic plasma exchange for severe COVID-19 acute respiratory distress syndrome with multiple organ failure - Keith, Philip (SAGE Open Med Case Rep, 2020)
The COVID-19 pandemic has brought about an urgent need for effective treatment, while conserving vital resources such as intensive care unit beds and ventilators. Antivirals, convalescent plasma, and biologics have been used with mixed results. The profound “cytokine storm” induced endotheliopathy and microthrombotic disease in patients with COVID-19 may lead to acute respiratory distress syndrome, sepsis, and multi-organ failure. We present a case of SARS-COV2 pneumonia with septic shock and multi-organ failure that demonstrated significant clinical improvement after therapeutic plasma exchange. A 65-year-old female with multiple comorbidities presented with progressive dyspnea and dry cough. She was found to be COVID-19 positive with pneumonia, and developed progressive hypoxemia and shock requiring vasopressors, cardioversion, and non-invasive positive pressure ventilation. Given her worsening sepsis with multi-organ failure, she underwent therapeutic plasma exchange with rapid clinical improvement. Her case supports the theory that plasma exchange may help abate the “cytokine storm” induced endotheliopathy and microthrombosis associated with COVID-19. Further studies are needed to identify markers of this pathway and the potential role of plasma exchange in these critically ill patients.